A note on movements of two fin whales (Balaenoptera physalus) tracked by satellite telemetry from the Faroe Islands in 2001 - Mikkelsen, Bjarni; Bloch , Dorete; Heide-Jørgensen, Mads Peter (J. Cetacean Res. Manage., 2023)
In August 2001, two fin whales were tagged with satellite linked radio transmitters 90km east of the Faroe Islands (62°N, 7°W). One whale that was tracked for 48 days resided on the Faroe shelf inside the 500m depth contour, with movements ranging within 190km from the tagging site. Another whale that was tracked for 116 days moved south to 46°N, 21°W, i.e. the same latitude as the Bay of Biscay, during the first 16 days of the tracking, which corresponds to a straight line distance of 2,830km. After residing at this latitude for three weeks, it moved northeast again, during two weeks, to an area north-west of Ireland. For the following two month period, it mainly moved within 54-58°N, at depths of 1,000-2,500m. A total of 132 positions were received from the two whales, most of relatively low accuracy, but still applicable for depicting large scale movements.